Remembering ORNAC’s 3rd President - ORNAC (Operating Room Nurses Association of Canada Journal, 2024)
Joan Donald RT, RN, BScN, BEd, MA(Ed), Ed.D., of Riverside, NB, passed away on August 22, 2022, after a courageous battle with ALS. She leaves behind her husband Hugh, daughter Stacey, and son Andrew. When ORNAC was formed in 1983, Joan was a member of the first executive and she soon became a member of the ORNAC Standards Committee where she was Chair from 1984 to 1986. She was also ORNAC’s third president (1988‐1990).